Análisis y optimización de un molino de trituración para envases desechables PET - Mayorga Sosa, Juan Francisco (2016)
This project aims to optimize and build a machine to grind PET disposable packaging. This machine will improve the quality of the grains obtained by establishing several speed parameters to analyze them. The speed variation will be established easily and manually by a variable speed drive and a potentiometer. This project contains the following chapter. Chapter 1 concerns about information about what is the procedure to recycle plastic waste that people spread in the environment and care in the form of recycling and raise awareness of its importance. It will discuss the characteristics of plastics and applications. Chapter 2 defines the needs of design. It is important in this project because it can get a prototype that fulfills the requirements for establishing the most appropriate alternatives for the machine. All of this starting from the selection of alternatives. Chapter 3 collects all the information on calculations that was obtained analytically. The information was collected from catalogs or books. Was got all this information respecting all the rules of design for the elaboration of a grinding mill. Chapter 4 is based on the results gathered through the variation of speed and the analysis of costs for the manufacture of the grinding mill respectively.